Fungal endo and exochitinase production, characterization, and application for Candida biofilm removal - de Menezes, Cíntia Lionela Ambrósio [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; da Silva, Ronivaldo Rodrigues [UNESP] (Springer Nature, 2024)
Chitinases are promising enzymes for a multitude of applications, including chitooligosaccharide (COS) synthesis for food and pharmaceutical uses and marine waste management. Owing to fungal diversity, fungal chitinases may offer alternatives for chitin degradation and industrial applications. The rapid reproduction cycle, inexpensive growth media, and ease of handling of fungi may also contribute to reducing enzyme production costs. Thus, this study aimed to identify fungal species with chitinolytic potential and optimize chitinase production by submerged culture and enzyme characterization using shrimp chitin. Three fungal species, Coriolopsis byrsina, Trichoderma reesei, and Trichoderma harzianum, were selected for chitinase production. The highest endochitinase production was achieved in C. byrsina after 168 h cultivation (0.3 U mL− 1). The optimal temperature for enzyme activity was similar for the three fungal species (up to 45 and 55 ºC for endochitinases and exochitinases, respectively). The effect of pH on activity indicated maximum hydrolysis in acidic pH (4–7). In addition, the crude T. reesei extract showed promising properties for removing Candida albicans biofilms. This study showed the possibility of using shrimp chitin to induce chitinase production and enzymes that can be applied in different industrial sectors.
Keywords: Bioeconomy; Chitin residue; Chitinolytic enzymes; Microbial enzymes; Submerged culture